Integrasi pendidikan islam dan sains dalam pandangan Muhammad Naquib Al Attas - Mujiburrohman; M. Erlin Susri (ARKA INSTITUTE, 2022)
This research is in the frame of religion and science in religion. Science and religion are often seen as contradictory. Science comes from empirical practice, religion comes from religious revelations. The figure of Nuqoib al Attas in chapter 20 tries to find a correlation between science and religion. Nuqoib al Attas succeeded in combining science and religion, both in concept and in real practice. This study seeks to find the methodological thinking of Nuqoib al Attas in terms of science and religion. This research is classified as library research with the main ingredients of manuscripts about Naquib al Attas. Data analysis using ethnography with text cultural background. The conclusion comes from the texts generated from the manuscripts found.